2017
DOI: 10.1016/j.ijmedinf.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Mobile application for diabetes self-management in China: Do they fit for older adults?

Abstract: Objectives Despite the exponential proliferation of Chinese diabetes applications, none are designed to meet the needs of the largest potential user population. The purpose of this study is to examine the features and contents of Chinese diabetes mobile applications in terms of their suitability for use by older adults with diabetes. Methods A search of the Apple application store and the 360 Mobile Assistant was conducted to identify Chinese diabetes applications. Next, we compared the features and contents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 35 publications
2
38
0
2
Order By: Relevance
“…However, despite the potential benefits and opportunities for elderly people to use mHealth application services, they are found to be less innovative toward it and encounter various challenges and difficulties when they are using mHealth applications. There are limited elderly users using mHealth application services to manage their health and the actual usage rate is still very low [ 4 , 5 , 6 ]. This is not conductive to the development of the mHealth industry and alleviates the medical pressures from the aging population.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the potential benefits and opportunities for elderly people to use mHealth application services, they are found to be less innovative toward it and encounter various challenges and difficulties when they are using mHealth applications. There are limited elderly users using mHealth application services to manage their health and the actual usage rate is still very low [ 4 , 5 , 6 ]. This is not conductive to the development of the mHealth industry and alleviates the medical pressures from the aging population.…”
Section: Introductionmentioning
confidence: 99%
“…Medical information and health promotion strategies can be remotely accessed by clients with smartphone applications (Gao, Zhou, Liu, Wang, & Bowers, 2017;Risso et al, 2016). WeChat public platform is currently most widely used (Feng et al, 2017;Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have highlighted the importance of using cellular facilities to educate the patient for self-care. 11,[25][26][27] The results of the software evaluation showed that all users were satisfied with the appearance and content features of the software and that it was comfortable to use. They also indicated that they would recommend the software to other type 2 diabetic patients.…”
Section: Discussionmentioning
confidence: 98%